Unusual morphologies and the occurrence of pseudomorphs after ikaite (CaCO3·6H2O) in fast growing, hyperalkaline speleothems. (1st May 2017) - Field, L. P.; Milodowski, A. E.; Shaw, R. P.; Stevens, L. A.; Hall, M. R.; Kilpatrick, A.; Gunn, J.; Kemp, S. J.; Ellis, M. A.
Unusual speleothems, associated with hyperalkaline (pH > 12) groundwaters have formed within a shallow, abandoned railway tunnel at Peak Dale, Derbyshire, UK. The hyperalkaline groundwaters are produced by the leaching of a thin layer (<2 m) of old lime-kiln waste on the soil-bedrock surface above the tunnel by rainwater. This results in a different reaction and chemical process to that more commonly associated with the formation of calcium carbonate speleothems from Ca-HCO3-type groundwaters and degassing of CO2. Stalagmites within the Peak Dale tunnel have grown rapidly (averaging 33 mm y–1), following the closure of the tunnel 70 years ago. They have an unusual morphology comprising a central sub-horizontally-laminated column of micro- to nano-crystalline calcium carbonate encompassed by an outer sub-vertical assymetric ripple-laminated layer. The stalagmites are composed largely of secondary calcite forming pseudomorphs (<1 mm) that we believe to be predominantly after the 'cold climate' calcium carbonate polymorph, ikaite (calcium carbonate hexahydrate: CaCO3·6H2O), with minor volumes of small (<5 μm) pseudomorphs after vaterite. The tunnel has a near constant temperature of 8–9°C, which is slightly above the previously published crystallization temperatures for ikaite (<6°C). Analysis of a stalagmite actively growing at the time of sampling, and preserved immediately within a dry nitrogen cryogenic vessel, indicates that following crystallization of ikaite, decomposition to calcite occurs rapidly, if not instantaneously. We believe this is the first occurrence of this calcium carbonate polymorph observed within speleothems.